2016
DOI: 10.1016/j.whi.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Access to Emergency Contraception in the Over-the-Counter Era

Abstract: Introduction After years of complex regulatory changes, levonorgestrel emergency contraception (LNG EC) is now approved for unrestricted sale in the US. Timely access to EC pills is critical because they are more likely to work the sooner they are taken. This study assesses whether LNG EC is sold in accordance with current Food and Drug Administration regulations. Methods We distributed an online questionnaire through an EC-focused listserv for reproductive health professionals, asking data collectors to vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 17 publications
(18 reference statements)
5
36
2
Order By: Relevance
“…Wilkinson's findings are similar to previous work by their group and others [2À10]. Findings from these mystery caller studies showed commonly that access was encouragingly high [1,3,5,7] but that pharmacy advice was not always accurate regarding product use or adverse effects [1,3,5,8,9]. Most importantly, many studies conducted after the 2014 legislative changes found misinformation was given about age restrictions [1,3,5,8À10].…”
supporting
confidence: 75%
“…Wilkinson's findings are similar to previous work by their group and others [2À10]. Findings from these mystery caller studies showed commonly that access was encouragingly high [1,3,5,7] but that pharmacy advice was not always accurate regarding product use or adverse effects [1,3,5,8,9]. Most importantly, many studies conducted after the 2014 legislative changes found misinformation was given about age restrictions [1,3,5,8À10].…”
supporting
confidence: 75%
“…LNG and UPA are suggested to have a similar safety profile, with serious adverse drug reactions essentially unknown [27][28][29]. But as LNG is approved as OTC much longer, more is known about its adverse effects through pharmacovigilance activities [30]. Potential reasons for concerns regarding the effective and safe use of EC.…”
Section: Discussionmentioning
confidence: 99%
“…Further, this study highlights numerous opportunities for pharmacy staff education, especially regarding citing incorrect age restrictions. Environmental changes, such as package labeling, and increased public awareness of LNG-EC access (Cleland, Bass, Doci & Foster, 2016) may further improve accessibility rates.…”
Section: Implications For Practice And/or Policymentioning
confidence: 99%